Upaya Kampanye Save The Children dalam Menangani Masalah Pernikahan Anak di Bangladesh Tahun 2020-2023 - Maharani, Farah; Hapsari, Renitha Dwi (Global Focus, 2024)
The issue of child marriage is a socio-economic problem that has existed for a long time in Bangladesh. Due to factors such as the economic crisis and prolonged school closures, the number of child marriage cases in Bangladesh has increased during the pandemic. The existing legal framework also cannot slow down the child marriage rates in Bangladesh. So this research tries to explain the efforts of Save The Children as an international non-governmental organization in dealing with the problem of child marriage in Bangladesh. This research explains how the Save The Children campaign is trying to deal with the problem of child marriage in Bangladesh in 2020-2023. The theory explained in this research is Brown's theory of international organizational campaign efforts. The research method uses qualitative data analysis techniques with descriptive research type. Primary data collection techniques from interviews with Rahamat Ullah from Save The Children in Bangladesh regarding the research topic. Research findings show that the Save The Children campaign's efforts to address the problem of child marriage are realized in the form of online campaigns via social media and offline campaigns. Apart from that, Save The Children also emphasizes children's participation in campaign efforts to address child marriage in Bangladesh.